Convective dissolution of CO2 in water and salt solutions - Thomas, Carelle; Dehaeck, Sam; De Wit, Anne (2018)
Dissolution of CO2 into saline aquifers can lead to the development of buoyancy-driven convection in the brine which enhances the efficiency of CO2 transfer. We analyze here experimentally the onset, development and dynamic properties of such convective fingering of CO2 into water, Antarctic water and in NaCl salt solutions of various concentrations to study the influence of varying the salt concentration on the buoyancy-driven convective dynamics. The convective dissolution pattern is visualized with the help of a schlieren imaging system sensitive to density gradients in the solution. We quantify the growth of convective fingers by performing, among others, a Fourier analysis of the pattern formation at early times and qualitatively study the nonlinear spatio-temporal dynamics at later times. In agreement with theoretical predictions, we find that increasing the salt concentration hinders the development of the instability as it delays the onset of convection, increases the wavelength of the convective pattern, decreases the growth rate and velocity of fingers as well as their interactions. Our experimental results provide quantitative data that should help the benchmarking of theoretical studies. SCOPUS: ar.j info:eu-repo/semantics/published